Perancangan Antena Quad-Ridged Horn pada Frekuensi 8 – 12 Ghz - Inosensius Imelian; Suwasti Broto; Yani Prabowo (Prosiding SISFOTEK, 2019)
Have been created a quad-ridge horn (QRH) antennas the working frequency at 8GHz - 12 GHz. This type of antenna is commonly used in the RADAR (Radio Detection And Ranging) and Detection Systems. The design results will be simulated using WIPL-D software to find out whether the design results are appropriate or not with the desired conditions. The next stage is the manufacture of antennas and the entire implementation of the fabrication carried out in the lathe service workshop to obtain precise size results. Because the size of the antenna is small (10cm - 20cm), with a thickness of ±10mm stainless-steel material, so it is not possible to do it alone. The quad-ridged horn antenna performance will be observed in testing using a vector network analyzer (VNA) measuring device whose working frequency ranges from 100KHz - 8.5GHz. The measurement results obtained, QRH antenna works at 8.33 GHz frequency. With the difference in antenna working frequency practically it will affect other variables such as return loss, VSWR, gain and antenna radiation diagram. This is due to differences in the dimensions of the antenna which has a shift in the value of several centimeters (cm) when in the fabrication process.